Application of enzymes as a diagnostic tool for soils as affected by municipal solid wastes. (15th May 2021) - Datta, Ankita; Gujre, Nihal; Gupta, Debaditya; Agnihotri, Richa; Mitra, Sudip
Abstract: Assessing the relationship between soil enzyme activities (SEAs) and heavy metals (HMs) without any amendment has rarely been conducted in soils contaminated with municipal solid wastes (MSW). Five soil enzymes [dehydrogenase (DHA), alkaline phosphatase (ALP), acid phosphatase (ACP), urease (UR), and nitrate reductase (NR)] have been assessed for HMs bioremediation using Zea mays L. grown in unamended soils that were contaminated with different types of MSW. Pot experiment was conducted for two seasons with soils collected from seven different locations within the MSW site. Experimental soil samples included a control (CA), contaminated by brick kiln wastes (SA1), kitchen and household wastes (SA2), medical wastes (SA3), mixed wastes (SA4), glass wastes (SA5), and metal scrap wastes (SA6). Rhizospheric soils were collected after the harvest of each season to investigate the impact of HMs on SEAs and physicochemical properties of soil. The results revealed an increase in DHA, ALP, and NR activities by 89.30%, 58.03% and 21.98% in SA1. Likewise, enhanced activities for UR (28.26%) and ACP (19.6%) were observed in SA3 and SA5 respectively. Insignificant increase in the macronutrients and organic carbon (OC) were also noted. The increased microbial count and the relatively higher amount of organic matter (OM) in the rhizosphere indicated the role of OM in HMs immobilization. Principal component analysis (PCA) indicated that DHA and NR are the important soil enzymes, underscored by their active involvement in the C and N turnover in the soil. Likewise, correlation analysis showed that DHA and NR activities were positively correlated with copper (Cu) (0.90, p < 0.01; 0.88, p < 0.01), suggesting its participation as a cofactor in enzymatic activities. In contrast, DHA was negatively correlated with cadmium (Cd) (−0.48, p < 0 0.05). Finally, these results indicated that in the absence of exogenous nutrient amendment, the SEAs were governed by OC, available nitrogen (Avl. N), Cu and Cd respectively. The study also highlighted the need for extensive research on SEAs for its utilization as a bioindicator in various soil bioremediation and quality management practices. Graphical abstract: Image 1 Highlights: Present study examined SEAs and its dynamics in MSW contaminated soil. Over time increase in SEAs observed even without any nutrient input. Organic matter promoted nutrient recycling under HM stress. DHA and NR activities significantly correlated with Cu. SEAs could be used as a bio-indicator for integrated soil management practices.